Сatatonia in Autism Spectrum Disorders: Diagnosis, Therapy and Clinical Science - D.M. Dhossche (Moscow State University of Psychology and Education, 2019)
Catatonia has been increasingly recognized as a comorbid syndrome of autism at a rate of 12-17% in adolescents and young adults with autism spectrum disorders. Symptoms that should alert the clinician for catatonia are markedly increased psychomotor slowness which may alternate with excessive motor activity, apparently purposeless, and not influenced by external stimuli, extreme negativism or muteness, stereotypy, peculiarities of voluntary movement, increased stereotypies with or without self-injury, echolalia, or echopraxia. Upsetting life events, the loss of routine and structure, experiences of loss, conflicts with parents, caregivers, or peers, and discrepancies between the ability in the patient and parental expectations-especially, in higher functioning autistic youth, are known to precipitate catatonia as well as medical and neurological illnesses. Lacking controlled trials, successful use of benzodiazepines, sometimes at high dosages, and electroconvulsive therapy for catatonia in autism is supported by case-reports and case-series. Electroconvulsive therapy is indicated for the treatment of catatonia when lorazepam does not bring about rapid relief. Maintenance electroconvulsive therapy is important for sustained symptom remission in some cases. There is an urgent need for prospective studies of catatonia in autism spectrum disorders and for controlled treatment trials.